Integrating Building Information Modelling into Construction Project Management Education in Australia: A Comprehensive Review of Industry Needs and Academic Gaps - Xavier Papuraj; Nima Izadyar; Zora Vrcelj (Buildings)
Integrating Building Information Modelling (BIM) into Construction Project Management (CPM) curricula is crucial for preparing industry-ready professionals with the digital competencies needed in the rapidly evolving, technology-driven construction sector. This systematic literature review evaluated gaps and challenges in BIM education within CPM courses, including limited faculty training, inconsistent curricula, and insufficient hands-on, interdisciplinary collaboration opportunities for students. These deficiencies hinder consistent BIM competency development among graduates, resulting in disparities in skill levels and readiness for industry demands. This study identified essential digital management skills and BIM competencies required for effective industry practice by examining global academic research. The findings revealed that despite advancing BIM adoption, significant gaps persist in its teaching, particularly the lack of collaborative education within project management disciplines, and need for enhanced collaboration between academia and the industry to bridge the skills gap. Industry professionals and academics emphasise the deficit in BIM knowledge among project management graduates and advocate for a cohesive educational framework aligning with industry requirements, emphasising hands-on experience and interdisciplinary collaboration. This study highlighted significant gaps and opportunities for integrating Building Information Modelling (BIM) into Construction Project Management (CPM) education, with the aim to enhance the competency and employability of future construction project managers. By proposing a phased approach and a BIM educational framework tailored to the Australian context, this review recommended the integration of BIM, supported by other emerging technologies, to better align educational outcomes with industry demands. The recommendations focus on curriculum design and implementation strategies to bridge the identified gaps.